Influence of sulphate and chloride ions on corrosion of 63-37 brass in aqueous ammonia containing copper - Rajasekharan Nair K.V.; Namboodhiri T.K.G. (My University, 2025)
The influence of copper added as metallic powder, cupric sulphate, or cupric chloride to 15·7M NH40H on the dissolution and tarnishing of 63-37 brass in this medium was studied using weight loss and electrochemical methods. Copper added as electrolytic metal powder accelerated the dissolution of brass in ammonia. The dissolution rate increased with increase in copper concentration to 4 g 1- 1, beyond which the rate decreased because of the formation of a black tarnish film. When copper was added as cupric sulphate or cupric chloride it was found that at low concentrations sulphate and chloride ions had no significant effect on the dissolution of brass, whereas at higher concentrations they enhanced dissolution. Both these ions prevented formation of the tarnish film on the brass surface. When copper was present in the ammonia the corrosion of brass occurred via a cathodically controlled process. The presence of SO24 and CI- produced high anodic dissolution currents. Open circuit potential values of the brass in these solutions and their variation with time were measured. The results are interpreted with reference to the chemistry of the systems under study. © 1988 Maney Publishing.